2020
DOI: 10.1681/asn.2019030274
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Sex Disparities in Catheter Use and Dialysis Access in the United States Medicare Population

Abstract: BackgroundDespite efforts to increase arteriovenous fistula and graft use, 80% of patients in the United States start hemodialysis on a central venous catheter (CVC).MethodsTo better understand in incident hemodialysis patients how sex and race/ethnicity are associated with time on a central venous catheter and transition to an arteriovenous fistula and graft, our observational cohort study analyzed US Renal Data System data for patients with incident ESKD aged ≥66 years who started hemodialysis on a CVC in Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
(65 reference statements)
0
25
0
1
Order By: Relevance
“…Persons categorized as Black and persons categorized as Latino, Latina, or Latinx will have hemodialysis initiated via autogenous fistula less often than will persons categorized as White, despite being younger and with fewer comorbidities. 31 In other analyses, persons categorized as Black had comparable rates of initiation via arteriovenous fistulas, 32 higher riskadjusted rates, 33 and greater rates of maturing arteriovenous grafts at the initiation of hemodialysis. 32 Persons categorized as Black, Latino, Latina, or Latinx, and womendwho constitute approximately one half of the end-stage renal disease populationdwill spend more time with a central venous catheter than will others.…”
Section: Reported Disparities In Peripheral Vascular Diseasesmentioning
confidence: 89%
See 2 more Smart Citations
“…Persons categorized as Black and persons categorized as Latino, Latina, or Latinx will have hemodialysis initiated via autogenous fistula less often than will persons categorized as White, despite being younger and with fewer comorbidities. 31 In other analyses, persons categorized as Black had comparable rates of initiation via arteriovenous fistulas, 32 higher riskadjusted rates, 33 and greater rates of maturing arteriovenous grafts at the initiation of hemodialysis. 32 Persons categorized as Black, Latino, Latina, or Latinx, and womendwho constitute approximately one half of the end-stage renal disease populationdwill spend more time with a central venous catheter than will others.…”
Section: Reported Disparities In Peripheral Vascular Diseasesmentioning
confidence: 89%
“…31 In other analyses, persons categorized as Black had comparable rates of initiation via arteriovenous fistulas, 32 higher riskadjusted rates, 33 and greater rates of maturing arteriovenous grafts at the initiation of hemodialysis. 32 Persons categorized as Black, Latino, Latina, or Latinx, and womendwho constitute approximately one half of the end-stage renal disease populationdwill spend more time with a central venous catheter than will others. 32 Symptomatic carotid disease.…”
Section: Reported Disparities In Peripheral Vascular Diseasesmentioning
confidence: 89%
See 1 more Smart Citation
“…A study on catheter use and dialysis access in the United States revealed that females and minorities spent more time on a central venous catheter, when compared with their male counterparts, despite efforts to transition patients to permanent access more quickly. 18 Another study demonstrated significant disparities in the presentation, management, and outcomes between males and females with acute myocardial infarctions. 19 One article even assessed the biological and environmental factors contributing to racial, ethnic, and sex disparities in vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This intersectionality between socio‐economic status, sex and gender extends to numerous other examples that demonstrate inequity in healthcare. Female patients undergoing dialysis spend a longer time with a central venous catheter and are less likely to transition to permanent access than men [20]. Women with an acute abdomen present later than men and are often referred to a gynaecologist, missing life‐threatening non‐obstetric causes; this gender‐linked delay in presentation and diagnosis has also been seen in patients with stroke, cancer and in women presenting with chest pain.…”
Section: Pregnancy and The Peripartum Periodmentioning
confidence: 99%